Designing a research methodology based on a theory of learning: a practical case in teacher training (2004)
In this lecture, an example of designing a research methodology based on a theory of learning will be presented. The example comes from a research project in pre-service mathematics teacher training. One of the studies in this project approached pre-service teachers' learning with Wenger's theory of social learning (1998). The sequence of going from a theory of learning to a research methodology leading to some research results will be discussed. This sequence involves the initial research problem definition, the analysis, interpretation and structuring of the theory giving rise to an initial set categories of analysis, a new definition of the research problem, the construction of a set of codes based on the categories of analysis, and the design of instruments for coding and analyzing the information. Some research results will be presented and the relationship between the results and the research problem and the theory of learning used will be discussed.